A Content Analysis of Cultural Representation in High School English Textbook in 2013 Education Curriculum - Fitri Rahmawati Astiandani; Oikurema Purwati (State Institute for Islamic Studies IAIN of Metro, 2021)
This study reports cultural content in the latest high school English textbook concerning the 2013 education curriculum. Besides, this paper also explores the intercultural communicative competence within the English textbooks. A qualitative research design is employed in this study. Moreover, the cultural contents and intercultural communicative competence were taken from the reading text on English textbooks for the last grade of senior high school entitled ‘Bahasa Inggris 2018 revised edition’. This study relied on the kind of cultural contents by Cortazzi & Jin (1999), types of cultural dimensions by Yuen (2011), and three levels of intercultural communicative competence by Byram (2002). It has been found that target culture with the cultural dimension of the product had a major proportion on the English textbook. Besides, the lowest level of intercultural communicative competence, namely basic cultural awareness was also discovered. In such a case, the complicity of intercultural values in the textbook should be given more attention so that students can easily grasp the values of various cultures. As a result, the aims of the 2013 education curriculum can be achieved well.